It is not just an academic experience: preservice teachers as long-term sojourners in a study abroad program in the USA. Issue 4 (13th August 2021) - Aslan, Reyhan; Bekereci-Şahin, Melike
Abstract : Purpose: This paper aims to focus on the long-term international experiences of a group of preservice English teachers who studied abroad as part of their training and recently returned home. Design/methodology/approach: Employing an interpretivist case study, five preservice English teachers participated in semi-structured, in-depth interviews. The participants were consulted to elicit feedback as the part of a member checking procedure. Findings: This study revealed that the participants' views of their international experience were primarily shaped by two main themes: (1) postsojourn outcomes: intercultural learning, professional learning and personal growth and (2) "bumps" in the road: struggles in capitalizing the learning opportunities. Originality/value: Recruiting students for extended study abroad programs alone without a concerted effort to address (inter)cultural learning and growth might not guarantee the quality and the outcomes of such programs. Based on the findings, the role of meaningful and intentional collaboration within the participant groups and between the partner institutions as well as critical reflection opportunities to assist prospective teachers through their growth in intercultural learning was discussed.